Case for NAFTA parity for CBI countries. - BERNAL, Richard (1996)
Discusses NAFTA's preferential access over the CBI, and NAFTA's effects on the US/Caribbean partnership. Argues that the Caribbean Basin Trade Security Act will provide for non-discriminatory access into the US for those products on which NAFTA gives Mexico an unintended advantage.